Current Advances and Challenges in Ocean Science-Feature Papers for the Founding of Oceans - Bode, Antonio; Lomas, Michael W.; Masqué, Pere; Macías, Diego (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue is designed to celebrate the founding of the open-access journal Oceans and is focused on presenting new ideas and advances at the cutting edge of ocean science. The scope of this Special Issue includes, but is not limited to: ocean geosciences, physics, biogeochemistry, and ecology; ocean ecosystem services and sustainable ocean resource use; and ocean operations and engineering. The fifteen articles published in this Special Issue focus on diverse areas of oceanography, including ocean ecology and biology, ocean geosciences, ocean climate and meteorology, ocean circulation, ocean chemistry and biogeochemistry, ocean resources (e.g., fisheries, aquaculture, and mining), ocean engineering, ocean modeling and ocean governance.